Are Suicide Attempters Wired Differently?: A Comparison With Nonsuicidal Depressed Individuals Using Plan Analysis. Issue 7 (July 2015) - Brüdern, Juliane; Berger, Thomas; Michel, Konrad; Maillart, Anja Gysin; Held, Isabelle Schmutz; Caspar, Franz
Abstract: Abstract: Limited research exists on internal risk processes in suicide attempters and factors that distinguish them from nonsuicidal depressive individuals. In this qualitative study, we investigated Plans, motives, and underlying self-regulatory processes of the two groups and conducted a comparative analysis. We analyzed narrative interviews of 17 suicide attempters and intake interviews of 17 nonsuicidal depressive patients using Plan Analysis. Then, we developed a prototypical Plan structure for both groups. Suicidal behavior serves various Plans found only in suicide attempters. Plans of this group are especially related to social perfectionism and withdrawal to protect their self-esteem. Depressive patients use several interpersonal control and coping strategies, which might help prevent suicidal behavior. The prototypical Plan structure of suicide attempters may be a valuable tool for clinicians to detect critical Plans and motives in their interaction with patients, which are related to suicide risk.